Pregnant patients diagnosed with COVID-19 simulate a clinical picture of preeclampsia - Ayvar, Sara L.; Aquino-Ruelas, Lizeth; Perez-Díaz, Miriam C.; Zepeda-Torres, José M.; Ancona-de la Rosa, Fanny Elizabeth; Martinez-Guerrero, Eva Emilia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
The current pandemic caused by the coronavirus 2019 (COVID-19) has been a relevant event; we have seen how it spreads rapidly and has an increased risk of becoming severe if the patient has any comorbidity. It is essential to consider that although COVID-19 is a respiratory disease, it can have systemic effects that can trigger various complications. This study is focused on how a COVID-19 infection can present symptoms similar to preeclampsia.